The Effect of Counseling on Mothers' Knowledge and Attitudes in Changing Mothers' Attitudes Regarding Baby Care Behavior by Musical Healthcare Providers - Syamsidar Syamsidar; Rifzul Maulina (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Baby massage performed by parents provides benefits that can foster parental self-confidence, improve the growth and development of babies. Lack of knowledge about the importance of implementing baby massage, so parents need to be provided with counseling about the benefits and correct techniques in baby massage. The purpose of this study was to determine the effect of baby massage counseling on the knowledge and attitudes of mothers in massaging babies at the Community Health Center. This study is a quantitative study, with the method used being a pre-experiment with a one-group pre-test and post-test design approach, with a total sample of 40 respondents using total sampling. Data collection techniques with observation sheets and questionnaires. Data were analyzed using the Wilcoxon signed-rank test. The results of this study obtained a value of þ = 0.000 < from α = 0.05 there indicating a significant difference in maternal knowledge before and after counseling, namely, from most of the mothers' knowledge of 70% less, increasing to the knowledge of most of the mothers of 72.5% who have good knowledge. The attitude of mothers before and after counseling was given, namely, the majority of mothers' attitudes 77.5% were negative, increasing to the majority of mothers' attitudes 70% were positive. The conclusion of this study is the influence of infant massage counseling on the knowledge and attitudes of mothers in massaging babies at the Community Health Center. The study is expected to provide benefits for the development of nursing science, provide an overview of the benefits of infant massage and how to massage babies correctly, and for further researchers to conduct infant massage counseling more than twice, so that all respondents who participate in infant massage counseling are not only motivated but skilled in massaging babies.